Bahasa Inggris Bahasa Inggris: Bahasa Indonesia - Maulana Nur Hidayatullah; Mulyono Aziz, Anton (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
The toll payment system in Indonesia has evolved using e-money since 2017. However, increasing vehicle populations and economic activities have caused congestion at toll gates, resulting in economic losses of up to IDR 4.4 trillion annually. To address this, the government plans to implement Multi Lane Free Flow (MLFF) technology, enabling transactions without stopping. The implementation requires thorough readiness, facing challenges such as recording accuracy between 80-99%, potential revenue loss for BUJT, regulatory uncertainties, delayed planning, and infrastructure needs. This study evaluates BUJT readiness using the Technology-Organization-Environment (TOE) framework, focusing on seven variables: Compatibility, Advantage, Complexity, Organization Readiness, Top Management Support, Government Support, and Vendor Quality. Using Partial Least Squares (PLS) and Structural Equation Modeling (SEM), data from purposive sampling of BUJT were analyzed. Results show only Advantage significantly affects readiness (t=2.496; p=0.013), with an R² of 0.24 indicating weak predictive power. The study contributes to understanding factors influencing BUJT readiness and recommends enhancing government support, stakeholder coordination, and technical and organizational preparedness evaluation.